Youth-led community organizing theory and action - Delgado, Melvin; Staples, Lee. (Oxford : Oxford University Press, 2008)
Youth-led organizing is increasingly receiving attention from scholars, activists, and the media. Delgado and Staples have produced the first comprehensive study of this dynamic field. Their well-organized book takes an important step toward bridging the gap between academic knowledge and community practice in this growing area.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Youth movements; Youth in development; Youth development; Community organization; Young volunteers in community development; Social action